Recommendations of the Association of the Scientific Medical Societies in Germany’s (AWMF) Ad-hoc Commission Medical Devices on the handling of medical devices after explantation - Markewitz, Andreas; Aschendorff, Antje; Mittelmeier, Wolfram; Asfour, Boulos; Berlis, Ansgar; Beyna, Torsten; Blohmer, Jens-Uwe; Gorenflo, Mathias; Katoh, Marcus; Knapp, Wolfram; Lenarz, Thomas; Spitzenberger, Folker; et al. (GMS German Medical Science)
The explantation of medical devices is a common procedure. However, the legal regulations and the resulting obligations of treating physicians and institutions regarding the handling of explanted medical devices are not always well known. The present recommendations aim to summarize the essential legal and practical aspects involved in the process following the explantation of medical devices.